2012
DOI: 10.1016/j.jcmg.2011.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Bone Marrow Mononuclear Cell Survival and Homing in Murine Peripheral Artery Disease

Abstract: Introduction Bone marrow mononuclear cell (MNC) therapy is a promising treatment for peripheral artery disease (PAD). This study aims to provide insight into cellular kinetics using molecular imaging following different transplantation methods. Methods and Results MNCs were isolated from F6 transgenic mice (FVB background) that express firefly luciferase (Fluc) and green fluorescence protein (GFP). Male FVB and C57Bl6 mice (n=50) underwent femoral artery ligation and were randomized into 4 groups receiving: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…This becomes even clearer when the fate of injected cells, and their rapid disappearance even from syngeneic mouse is taken into account [609]. A very comprehensive review on the use of various immunocompromised mouse strains in hind limb ischemia models for human cell therapy validations has recently been published by Thomas et al [594] and provides valuable information on the choice of the proper model.…”
Section: Mouse Hind Limb Ischemia Modelmentioning
confidence: 99%
“…This becomes even clearer when the fate of injected cells, and their rapid disappearance even from syngeneic mouse is taken into account [609]. A very comprehensive review on the use of various immunocompromised mouse strains in hind limb ischemia models for human cell therapy validations has recently been published by Thomas et al [594] and provides valuable information on the choice of the proper model.…”
Section: Mouse Hind Limb Ischemia Modelmentioning
confidence: 99%
“…Even when cells were injected in a hindlimb ischemia model, the results were not much different. Bioluminescent imaging (BLI) demonstrated that mesenchymal stem cells (MSCs) which were transplanted into ischemic hindlimbs disappeared by day 6 [35] or 20 [36]. Similarly, hPSC-derived ECs showed no detectable bioluminescence signals after 14 days in a hindlimb ischemia model [37].…”
Section: Use Of Biomaterials To Improve Cell Survival In Vivomentioning
confidence: 99%
“…Similar trends were observed when cells were injected into a hindlimb ischemia model. Monitoring of cell survival using bioluminescent imaging (BLI) demonstrated that mesenchymal stem cells (MSCs) disappeared by 6 days 10 or 20 days 11 post cell transplantation. Survival of hPSC-ECs in a hindlimb ischemia model was reported by only one study, which showed no detectable bioluminescence signals after 14 days 12 .…”
Section: Introductionmentioning
confidence: 99%